2010
DOI: 10.1111/j.1751-7915.2010.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of aerobic anoxygenic phototrophic bacteria in paddy soil and their response to elevated atmospheric CO2

Abstract: SummaryAerobic anoxygenic phototrophic bacteria (AAnPB) are recognized as an important group driving the global carbon cycling. However, the diversity of AAnPB in terrestrial environment remains largely unknown as well as their responses to the elevated atmospheric CO2. By using culture‐independent techniques, the diversity of AAnPB in paddy soil and the changes in response to the rising atmospheric CO2 were investigated within China FACE (Free‐air CO2 enrichment) platform. There was a phylogenetically diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The remainder of the PufM diversity in our samples, although recovered in small relative numbers, also mainly related to aquatic photoheterotrophic taxa. However, several of the PufM sequences recovered (e.g., Methylobacterium -like, Rhodopseudomonas -like) were highly similar to PufM reported from Arctic soils (Feng et al, 2014) or Chinese paddy soils (Feng et al, 2009, 2011a,b,c). Thus, although aerobic anoxygenic phototrophy is frequently studied in aquatic environments, our data strongly suggest that this lifestyle may potentially be important in terrestrial ecosystems.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The remainder of the PufM diversity in our samples, although recovered in small relative numbers, also mainly related to aquatic photoheterotrophic taxa. However, several of the PufM sequences recovered (e.g., Methylobacterium -like, Rhodopseudomonas -like) were highly similar to PufM reported from Arctic soils (Feng et al, 2014) or Chinese paddy soils (Feng et al, 2009, 2011a,b,c). Thus, although aerobic anoxygenic phototrophy is frequently studied in aquatic environments, our data strongly suggest that this lifestyle may potentially be important in terrestrial ecosystems.…”
Section: Discussionsupporting
confidence: 62%
“…Under these new atmospheric conditions, many of the anaerobic anoxygenic phototrophic bacteria may have disappeared from the now oxygenated habitats, although some groups adapted and embarked on an aerobic lifestyle (Koblížek, 2015). These aerobic anoxygenic phototrophic bacteria (AAP) were first reported in 1978 (Harashima et al, 1978) and are defined as aerobic species that synthesize bacteriochlorophyll and use light energy as an auxiliary energy source for their mostly heterotrophic metabolism (Feng et al, 2011a; Koblížek, 2015). Moreover, they do not contain carbon fixation enzymes (Yurkov and Csotonyi, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…But interestingly, we not only found the negative indirect effects, but also found that elevated CO 2 could directly change the community structure of microorganism and significantly increased the microbial biomass of soil in both E. urophylla and A. mearnsii . Similarly, some studies found elevated CO 2 significantly increased the biomass of soil in non-rhizosphere soil or bulk soil [41, 42]. Although the exact mechanisms behind the direct effect are not well known, we believe that the ratio of gases in the atmosphere may cause the changes in soil surface moisture or soil respiration.…”
Section: Discussionmentioning
confidence: 62%
“…Recently, Gemmatimonas phototrophica was found to harbor a photosynthesis gene cluster of proteobacterial origin [34][35] and phototrophic Gemmatimonadetes bacteria consisting of 0.4-11.9% of whole phototrophic microbial communities in their habitats [36]. The habitats for AAP bacteria are as diverse as marine environments, freshwater lakes, saline lakes, soda lakes, and soils [37][38][39][40]. The complex interplay of local contemporary environmental effects and dispersal limitations contribute to the distribution of anoxygenic phototrophs.…”
Section: Diversity Of Pufm Gene Populationsmentioning
confidence: 99%